Analisis Faktor-Faktor yang Memengaruhi Nilai Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Devi, Ni Luh Nyoman Sherina; Manuari, Ida Ayu Ratih (E-Jurnal Akuntansi; Vol 31 No 12 (2021)DO - 10.24843/EJA.2021.v31.i12.p09, 2021)
Firm value is closely related to shareholder wealth and become the main focus of investor decision making. This study analyzes the impact of capital design, productivity, profit strategy, firm development, also, firm size on the value of assembling organizations. Purposive testing technique was utilized and gotten 47 assembling organizations with 3 years perception, with all out 141 examples. Various direct relapse examination was utilized as a scientific procedure in this review. Results showed that profitability positively affected firm worth. While capital design, profit strategy, firm development, and firm size were found to have no impact on firm worth. Organizations are encouraged to improve and focus closer on factors, for example, productivity that can influence the worth of the organization. Keywords : The Worth of the Organization; Capital Construction; Dividend Strategy; Profitability; Company Development; Company Size.